Tracing the Jerusalem Code Volume 3: The Promised Land Christian Cultures in Modern Scandinavia (ca. 1750-ca. 1920) - Zorgati, Ragnhild J.; Bohlin, Anna; Sjøvoll, Therese (De Gruyter, 2021)
With the aim to write the history of Christianity in Scandinavia with Jerusalem as a lens, this book investigates the image - or rather the imagination - of Jerusalem in the religious, political, and artistic cultures of Scandinavia through most of the second millennium. Volume III analyses the impact of Jerusalem on Scandinavian Christianity from the middle of the 18. century in a broad context.